Nickel-molybdenum alloy self-supporting catalytic electrode, preparation method thereof and application of nickel-molybdenum alloy self-supporting catalytic electrode in water electrolysis hydrogen production, carbon dioxide electrochemical reduction or nitrate electrochemical reduction
The viscosity and deposition current density of the electrodeposited fluid are regulated by one-step electrodeposition method, and nickel and molybdenum ions are co-deposited to prepare a nickel-molybdenum catalytic electrode with high catalytic activity and stability, which solves the problem of low catalytic activity and preparation in the prior art. The problem of high process risk has achieved efficient and safe catalytic electrode preparation.
Patent Information
- Application Number
- CN202411562358.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-04
AI Technical Summary
In the prior art, the catalytic activity of the nickel-molybdenum alloy catalytic electrode has low catalytic activity, small specific surface area, insufficient stability, and high energy consumption and high risk in the preparation process.
A nickel-molybdenum alloy self-supported catalytic electrode was prepared by one-step electrodeposition method. By regulating the viscosity and deposition current density of the electrodeposited liquid, co-deposition of nickel ions and molybdenum ions was achieved, forming a nickel-molybdenum catalyst with high catalytic activity and stability.
It realizes the preparation of high-performance hydrogen evolution catalytic electrodes. The raw materials do not contain precious metals, easy to control operating conditions, simple industrial processes, high safety and low energy consumption, and is suitable for large-scale low-cost industrial manufacturing.
Smart Images

Figure CN119465254A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nickel-molybdenum alloy self-supporting catalytic electrode, a preparation method thereof and application thereof in hydrogen production by electrolysis of water, electrochemical reduction of carbon dioxide or electrochemical reduction of nitrate, and belongs to the technical field of catalytic electrode preparation. Background Art
[0002] The intermittent and unstable nature of renewable energy sources such as wind power makes energy storage very important. Hydrogen, as an energy storage medium, has the advantages of being pollution-free and having high energy density. As an almost zero-pollution method of hydrogen production, water electrolysis has the advantages of high hydrogen purity (over 99.9%) and simple raw material acquisition. However, compared with "gray hydrogen" prepared from fossil fuels by traditional methods, the cost of "green hydrogen" prepared by water electrolysis is 7 to 15 times higher. Such high cost mainly comes from the high investment required for the electrolyzer and the high energy consumption during the electrolysis process.
[0003] The electrolysis of water in an alkaline environment significantly reduces the cost of the electrolyzer due to the use of non-precious metal catalytic electrodes. However, the catalytic activity of non-precious metal electrodes is usually much lower than that of precious metal catalytic electrodes. Therefore, it is of great significance to develop non-precious metal-based self-supporting hydrogen evolution catalytic electrodes with high catalytic activity and easy preparation.
[0004] Among many non-precious metal electrodes, nickel-molybdenum alloy is considered to be a promising non-precious metal hydrogen evolution catalytic electrode due to its simple composition and excellent catalytic performance. The nickel-molybdenum alloy catalytic electrodes reported in existing patents are mainly the following: (1) nickel-molybdenum powder; (2) nickel-molybdenum foam. When preparing metal solid solutions by sintering method, nickel-molybdenum alloy prepared by nickel-molybdenum powder or nickel-molybdenum foam is usually used, but its specific surface area is small and the catalytic activity is not high. (3) Self-supporting nickel-molybdenum alloy catalytic electrode is prepared by high-temperature reduction process in the reducing atmosphere of hydrogen or ammonia. The high-temperature reduction method can obtain NiMo alloy hydrogen evolution catalyst with high catalytic activity and large specific surface area. However, the preparation process uses hydrogen or ammonia as a reducing agent, which is dangerous and energy-intensive. (4) Nickel-molybdenum alloy is deposited on the electrode surface by electrochemical method. For example, in order to overcome the problem of large precipitation potential of nickel and molybdenum in the electrodeposition method used in patents CN116752173A and CN116145172A, a coordination agent is added and the pH value is adjusted to 100mA·cm -2 The nickel-molybdenum alloy was prepared by electrodeposition at a current density of . However, the prepared catalytic electrode has the defects of low catalytic activity, small specific surface area and insufficient stability.
[0005] Therefore, it is urgent to research and develop new technologies and methods to prepare non-precious metal catalytic electrodes with nickel and molybdenum as the main components, which have excellent catalytic properties and are suitable for large-scale manufacturing under mild conditions. Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a nickel-molybdenum alloy self-supporting catalytic electrode and a preparation method thereof and its application in hydrogen production by electrolysis of water, electrochemical reduction of carbon dioxide or electrochemical reduction of nitrate. The "one-step" electrodeposition process for preparing the self-supporting catalytic electrode does not contain precious metals in the raw materials, the operating conditions are easy to control, the industrial process is simple, the safety is good, the energy consumption is low, and it is suitable for large-scale low-cost industrial manufacturing.
[0007] To achieve the above-mentioned object, the present invention provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, which comprises: placing a copper-based metal material and / or a nickel-based metal material in an electrodeposition solution for electrochemical deposition to obtain a nickel-molybdenum alloy self-supporting catalytic electrode; the electrodeposition solution comprises a nickel salt-molybdenum salt-supporting electrolyte mixed solution; the nickel salt-molybdenum salt-supporting electrolyte mixed solution comprises a supporting electrolyte, a nickel salt and a molybdenum salt; during the electrochemical deposition process, the current density is 1 to 2 A·cm -2 ; or, during electrochemical deposition, the current density is greater than or equal to 0.2A·cm -2 , less than 1A·cm -2 The electrodeposition solution includes a first thickener. Taking 100 mL of the electrodeposition solution as 100%, the mass fraction of the first thickener is 10 to 60%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%.
[0008] The present invention uses supporting electrolyte, nickel salt and molybdenum salt as raw materials, and utilizes the method of regulating the viscosity of the electrodeposition liquid and the deposition current to achieve the purpose of controlling the electrodeposition process, so that diffusion rather than reaction kinetics becomes the rate-controlling step of the deposition process, so that nickel ions and molybdenum ions with large thermodynamic precipitation potential differences are reduced, and nickel ions and molybdenum ions are precipitated at the same time, forming a nickel-molybdenum alloy catalytic electrode with good catalytic activity and stability on the metal surface. On the one hand, the present invention increases the deposition current density to 1-2A·cm -2 On the other hand, the present invention increases the viscosity of the system by adding a first thickener to the electrodeposition solution to achieve a low energy consumption of 0.2 to 1 A·cm -2 (Not including 1A·cm -2 ) The co-deposition of nickel and molybdenum ions can be achieved even at low current density. The present invention realizes the preparation of high-performance hydrogen evolution catalytic electrode by one-step electrodeposition method, the raw materials do not contain precious metals, the operating conditions are easy to control, the industrial process is simple, the safety is better, the energy consumption is lower, and it is suitable for large-scale low-cost industrial manufacturing.
[0009] In a preferred embodiment, the electrodeposition solution further comprises a second thickener and / or a surfactant; the first thickener and the second thickener are independently selected from one or a combination of two or more of glycerol, ethylene glycol, sodium carboxymethyl cellulose, xanthan gum, gelatin and sodium alginate. The surfactant is selected from one or a combination of two or more of lauryl alcohol, sodium dodecyl sulfate, 4-(1,1,3,3-tetramethylbutyl)phenyl-polyethylene glycol (Triton X-100) and polyoxyethylene sorbitan monolaurate (polysorbate 20).
[0010] The present invention adds a second thickener and / or a surfactant to the electrodeposition liquid. The introduction of the second thickener can regulate the viscosity of the electrodeposition liquid, further change the diffusion rate of nickel ions and molybdenum ions in the electrodeposition liquid, and is used to optimize the nickel-molybdenum ratio of the catalytic electrode and the surface morphology of the catalytic electrode, thereby further optimizing the catalytic activity and stability of the catalytic electrode. Among them, the introduction of the second thickener can increase the viscosity of the system, thereby reducing the diffusion rate of ions, increasing the intrinsic diffusion difference of nickel and molybdenum, and then increasing the nickel-molybdenum ratio; at the same time, the introduction of the second thickener will form a slower diffusion behavior, which helps to reduce the particle diameter formed on the metal surface, thereby increasing the specific surface area of the catalytic electrode. The excellent nickel-molybdenum ratio and specific surface area further improve the catalytic activity and stability of the catalytic electrode. The introduction of the surfactant can make the bubble generation in the electrodeposition process more gentle, which is conducive to crystal formation.
[0011] Furthermore, based on 100 mL of the electrodeposition liquid as 100%, the mass fraction of the first thickener and the second thickener is 2 to 60%, for example, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%.
[0012] Furthermore, in the electrodeposition solution, the concentration of the surfactant is 0.2 to 5 mmol / L, for example, 0.2 mmol / L, 1 mmol / L, 2 mmol / L, 3 mmol / L, 4 mmol / L or 5 mmol / L.
[0013] In a preferred embodiment, before placing the conventional copper-based metal material and / or nickel-based metal material in an electrodeposition solution for electrochemical deposition, the preparation method includes placing the copper-based metal material and / or nickel-based metal material in a hydrochloric acid aqueous solution for ultrasonic washing. Washing can further remove impurities and oxide layers on the surface of the material to facilitate subsequent electrochemical deposition. Further, the concentration of hydrochloric acid in the hydrochloric acid aqueous solution is 0.5 to 3 mol / L. Further, the ultrasonic washing time is 10 to 30 min.
[0014] In some optional embodiments, the copper-based metal material is selected from one or a combination of two or more of copper foam, copper mesh, copper fiber felt, copper sheet and copper foil. The nickel-based metal material is selected from one or a combination of two or more of nickel mesh, nickel sheet, nickel foam and nickel foil.
[0015] In a preferred embodiment, the electrodeposition liquid is prepared by the following steps: preparing a solution containing a supporting electrolyte and a nickel salt with water, adding a molybdenum salt to the solution, and optionally adding a buffer solution to adjust the pH value of the system to 4.0-6.0, and then optionally adding a surfactant, a first thickener, and a second thickener to the solution, stirring and dissolving, to obtain the electrodeposition liquid.
[0016] Furthermore, in the electrodeposition solution, the concentration of the supporting electrolyte is 0.5 to 3 mol / L, for example, 0.5 mol / L, 1 mol / L, 2 mol / L or 3 mol / L; the concentration of the nickel salt is 0.05 to 0.2 mol / L, for example, 0.05 mol / L, 0.1 mol / L or 0.2 mol / L; the concentration of the molybdenum salt is 0.025 to 0.1 mol / L, for example, 0.025 mol / L, 0.05 mol / L or 0.1 mol / L.
[0017] In some optional embodiments, the nickel salt is selected from one or a combination of two or more of nickel chloride, nickel sulfate (e.g., nickel sulfate hexahydrate), nickel acetate and nickel nitrate; the molybdenum salt is selected from one or a combination of two or more of sodium molybdate dihydrate, ammonium molybdate heptahydrate, potassium molybdate and lithium molybdate.
[0018] Furthermore, the buffer solution is selected from one or a combination of two or more of an ammonium salt solution, a boric acid solution, and an acetic acid solution. The ammonium salt in the ammonium salt solution includes one or a combination of two or more of ammonium chloride, ammonium sulfate, and ammonium acetate.
[0019] Further, the supporting electrolyte includes one or more combinations of ammonium salts, sodium salts and potassium salts. Among them, the ammonium salt is selected from one or more combinations of ammonium acetate, ammonium sulfate and ammonium chloride; the sodium salt is selected from one or more combinations of sodium acetate, sodium chloride and sodium sulfate; the potassium salt is selected from one or more combinations of potassium chloride, potassium sulfate and potassium acetate. In some optional embodiments, when the supporting electrolyte is an ammonium salt, it is not necessary to add excess buffer solution; when the supporting electrolyte is one or more combinations of sodium sulfate, sodium chloride, potassium sulfate or potassium chloride, the buffer solution used is boric acid solution; when the supporting electrolyte is sodium acetate and / or potassium acetate, the buffer solution used is acetic acid solution to form a buffer pair to adjust the pH.
[0020] In a preferred embodiment, the above-mentioned electrodeposition solution is placed in a two-electrode electrolytic cell, and the copper-based metal material and / or nickel-based metal material is used as the cathode and the graphite electrode is used as the anode for electrochemical deposition. The electrodeposition method adopts constant current. After the electrodeposition is completed, the electrode is taken out, rinsed with deionized water 2 to 3 times, rinsed with ethanol once, and dried naturally.
[0021] Furthermore, during the electrochemical deposition process, the electrochemical deposition time is 3 to 120 minutes, for example, 3 minutes, 10 minutes, 30 minutes, 50 minutes, 70 minutes, 90 minutes or 120 minutes. During the electrochemical deposition process, the temperature is room temperature, without any special limitation.
[0022] The present invention also provides a nickel-molybdenum alloy self-supporting catalytic electrode, which is prepared by the above-mentioned method for preparing the nickel-molybdenum alloy self-supporting catalytic electrode.
[0023] The present invention also provides an application of the aforementioned nickel-molybdenum alloy self-supporting catalytic electrode in the process of hydrogen production by electrolysis of water, electrochemical reduction of carbon dioxide and electrochemical reduction of nitrate.
[0024] The nickel-molybdenum hydrogen evolution catalytic electrode prepared by the method provided by the present invention has high catalytic activity and stability, and can be widely used as a hydrogen evolution electrode in the electrolysis of water to produce hydrogen, the electrochemical reduction of carbon dioxide, and the electrochemical reduction of nitrates. For example, the above-mentioned nickel-molybdenum alloy self-supporting hydrogen evolution catalytic electrode is used for the electrolysis of water to produce hydrogen, and is used as a hydrogen evolution and / or oxygen evolution electrode in an alkaline solution, and the alkaline solution is a 0.1-7 mol / L potassium hydroxide aqueous solution or a sodium hydroxide aqueous solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The hydrogen evolution polarization curves of the nickel-molybdenum hydrogen evolution catalytic electrodes prepared in Example 1-1, Example 2, Example 3 and Comparative Example 1, and the Pt / C electrode containing the precious metal platinum are shown (all after 100% iR compensation);
[0026] Figure 2 The nickel-molybdenum hydrogen evolution catalytic electrodes prepared in Example 1-1, Example 2, Example 3 and Comparative Example 1, and hydrogen evolution overpotential diagrams of a Pt / C electrode containing precious metal platinum at different current densities (all after 100% iR compensation);
[0027] Figure 3 The X-ray diffraction pattern of the nickel-molybdenum hydrogen evolution catalytic electrode prepared in Example 2 is shown;
[0028] Figure 4 The electrochemical active areas of the nickel-molybdenum hydrogen evolution catalytic electrodes prepared in Example 1-1, Example 2, Example 3 and Comparative Example 1, and the Pt / C electrode containing the precious metal platinum are shown;
[0029] Figure 5 The hydrogen evolution polarization curves (100% iR compensation) of the nickel-molybdenum hydrogen evolution catalytic electrode prepared in Example 1-1, Example 4 and Comparative Example 1, and the Pt / C electrode containing the precious metal platinum are shown;
[0030] Figure 6 The constant current stability test diagram of the nickel-molybdenum hydrogen evolution catalytic electrode prepared in Example 2 is shown;
[0031] Figure 7 The hydrogen evolution polarization curves of the nickel-molybdenum alloy self-supporting catalytic electrodes prepared in Examples 5 to 8 and the Pt / C electrode containing precious metal platinum (100% iR compensation) are shown;
[0032] Figure 8 The catalytic electrodes prepared in Example 9-1, Example 9-2 and Example 9-3, and the hydrogen evolution polarization curves of the Pt / C electrode containing the precious metal platinum (100% iR compensation) are shown;
[0033] Fig. 9 Scanning electron microscope images of nickel-molybdenum hydrogen evolution catalytic electrodes prepared in Example 1-1, Example 1-2, Example 3 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0034] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0035] Example 1
[0036] Example 1-1
[0037] This embodiment provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0038] (1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0039] (2) Prepare 100 mL of a solution with a concentration of 2 mol / L ammonium chloride and a concentration of 0.1 mol / L nickel chloride with deionized water. The solution is green in color. Add 0.005 mol of sodium molybdate dihydrate to the solution and dissolve it to obtain an electrodeposition solution. Since nickel chloride reacts with sodium molybdate to form sodium molybdate precipitate, the solution is unstable and should be used immediately after preparation.
[0040] (3) The clean copper foam obtained above was used as the cathode and the graphite electrode was used as the anode, and placed in the above electrodeposition solution at 2A·cm -2Electrodeposition was performed for 30 minutes at a current density of . A large amount of precipitation was generated during the deposition process, which was nickel molybdate. After the deposition was completed, the catalytic electrode was taken out from the electrodeposition solution, washed with deionized water, then washed with ethanol, and left to dry, thus obtaining a nickel-molybdenum alloy self-supporting catalytic electrode.
[0041] Example 1-2
[0042] This embodiment provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0043] (1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0044] (2) Prepare 100 mL of a solution with a concentration of 2 mol / L ammonium chloride and a concentration of 0.1 mol / L nickel chloride with deionized water. The solution is green in color. Add 0.005 mol of sodium molybdate dihydrate to the solution and dissolve it to obtain an electrodeposition solution. Since nickel chloride reacts with sodium molybdate to form sodium molybdate precipitate, the solution is unstable and should be used immediately after preparation.
[0045] (3) The clean copper foam obtained above was used as the cathode and the graphite electrode was used as the anode, and placed in the above electrodeposition solution at 2A·cm -2 Electrodeposition was performed for 30 minutes at a current density of , and a magnetic anode was added for stirring during the electrodeposition process (the stirring rate was 200 rpm). A large amount of precipitation was generated during the deposition process, and the precipitation was nickel molybdate. After the deposition was completed, the catalytic electrode was taken out from the electrodeposition solution, washed with deionized water, then washed with ethanol, and left to dry, thus obtaining a nickel-molybdenum alloy self-supporting catalytic electrode.
[0046] Example 2
[0047] This embodiment provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0048] 1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0049] 2) Prepare 100 mL of a solution with a concentration of 2 mol / L ammonium chloride and a concentration of 0.1 mol / L nickel chloride with deionized water. The solution is green in color. Add 0.005 mol of sodium molybdate dihydrate to the solution, stir and dissolve. Add lauryl alcohol to the solution until the concentration of lauryl alcohol is 1 mmol / L to obtain an electrodeposition solution. Since nickel chloride reacts with sodium molybdate to form sodium molybdate precipitate, the solution is unstable and should be used immediately after preparation.
[0050] 3) The clean copper foam obtained above was used as the cathode and the graphite counter electrode was used as the anode, and placed in the above electrodeposition solution at 2A·cm -2 Electrodeposition was performed for 30 minutes at a current density of . A large amount of precipitate was generated during the deposition process, which was nickel molybdate. After the deposition was completed, the catalytic electrode was taken out from the electrodeposition solution, washed with deionized water, then washed with ethanol, and left to dry to obtain a nickel-molybdenum alloy self-supporting catalytic electrode.
[0051] Example 3
[0052] This embodiment provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0053] 1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0054] 2) Prepare 100 mL of a solution with a concentration of 2 mol / L ammonium chloride and a concentration of 0.1 mol / L nickel chloride with deionized water. The solution is green in color. Add 0.005 mol of sodium molybdate dihydrate to the solution, stir and dissolve. Add ethylene glycol to the solution until the concentration of ethylene glycol is 4 mol / L to obtain an electrodeposition solution. Since nickel chloride reacts with sodium molybdate to form sodium molybdate precipitate, the solution is unstable and should be used immediately after preparation.
[0055] 3) The clean copper foam obtained above was used as the cathode and the graphite counter electrode was used as the anode, and placed in the above electrodeposition solution at 2A·cm -2 Electrodeposition was performed for 30 minutes at a current density of . A large amount of precipitate was generated during the deposition process, which was nickel molybdate. After the deposition was completed, the catalytic electrode was taken out from the electrodeposition solution, washed with deionized water, then washed with ethanol, and left to dry to obtain a nickel-molybdenum alloy self-supporting catalytic electrode.
[0056] Example 4
[0057] This embodiment provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0058] 1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0059] 2) Prepare 100 mL of a solution with a concentration of 2 mol / L ammonium chloride and a concentration of 0.1 mol / L nickel chloride with deionized water. The solution is green in color. Add 0.005 mol of sodium molybdate dihydrate to the solution, stir and dissolve, and obtain an electrodeposition solution. Since nickel chloride reacts with sodium molybdate to form sodium molybdate precipitate, the solution is unstable and should be used immediately after preparation.
[0060] 3) The clean copper foam obtained above was used as the cathode and the graphite counter electrode was used as the anode, and placed in the above electrodeposition solution at 1A·cm -2 Electrodeposition was performed for 30 minutes at a current density of . A large amount of precipitate was generated during the deposition process, which was nickel molybdate. After the deposition was completed, the catalytic electrode was taken out from the electrodeposition solution, washed with deionized water, then washed with ethanol, and left to dry to obtain a nickel-molybdenum alloy self-supporting catalytic electrode.
[0061] Comparative Example 1
[0062] This comparative example provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0063] 1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0064] 2) Prepare 100 mL of a solution with a concentration of 2 mol / L ammonium chloride and a concentration of 0.1 mol / L nickel chloride with deionized water. The solution is green in color. Add 0.005 mol of sodium molybdate dihydrate to the solution, stir and dissolve, and obtain electrodeposition solution 1. Since nickel chloride reacts with sodium molybdate to form sodium molybdate precipitate, the solution is unstable and should be used immediately after preparation.
[0065] 3) The clean copper foam obtained above was used as the cathode and the graphite counter electrode was used as the anode, and placed in the above electrodeposition solution at 0.5 A·cm -2 Electrodeposition was performed for 30 minutes at a current density of . A large amount of precipitate was generated during the deposition process, which was nickel molybdate. After the deposition was completed, the catalytic electrode was taken out from the electrodeposition solution, washed with deionized water, then washed with ethanol, and left to dry to obtain a nickel-molybdenum alloy self-supporting catalytic electrode.
[0066] The surface element contents of the nickel-molybdenum alloy self-supporting catalytic electrodes under different preparation conditions in Example 1-1, Example 1-2, and Example 3 are shown in Table 1.
[0067] Table 1
[0068]
[0069] Based on the above analysis of the transfer behavior during the deposition process, it is shown that by adjusting the diffusion behavior, the purpose of adjusting the ratio of nickel and molybdenum atoms in electrolysis can be achieved, thereby adjusting the catalytic performance. The stirring process can accelerate the mass transfer behavior in the solution, and the intrinsic diffusion difference between Ni and Mo is reduced, thereby reducing the nickel-molybdenum atomic ratio; by adding ethylene glycol to increase the viscosity and thus reduce the diffusion rate of ions, the intrinsic diffusion difference of nickel and molybdenum is increased, thereby increasing the nickel-molybdenum atomic ratio, and the preferred nickel-molybdenum ratio range is 2 to 8:1. But overall, in Example 1 and Example 3, the three conditions of "standing" (Example 1-1), "stirring" (Example 1-2), and "adding ethylene glycol" (Example 3) are respectively adopted, and a nickel-molybdenum alloy self-supporting catalytic electrode with good performance can be obtained.
[0070] The nickel-molybdenum hydrogen evolution catalytic electrodes prepared in Example 1-1, Example 2, Example 3, Example 4 and Comparative Example 1, and the Pt / C electrode containing the precious metal platinum were used as working electrodes, graphite was used as a counter electrode, and a mercury / mercury oxide electrode was used as a reference electrode, and electrochemical tests were carried out in a 1 mol / L potassium hydroxide aqueous solution.
[0071] Figure 1 The hydrogen evolution polarization curves of the nickel-molybdenum hydrogen evolution catalytic electrodes prepared in Example 1-1, Example 2, Example 3 and Comparative Example 1, and the Pt / C electrode containing the precious metal platinum are shown (all after 100% iR compensation).
[0072] Figure 2 The results show that the two current densities of 100 mA cm -2 , 500mA·cm -2 The hydrogen evolution overpotentials of the nickel-molybdenum hydrogen evolution catalytic electrodes prepared in Example 1-1, Example 2, Example 3 and Comparative Example 1, and the Pt / C electrode containing precious metal platinum at different current densities (all after 100% iR compensation). The results show that the nickel-molybdenum hydrogen evolution catalytic electrodes prepared in Example 1-1, Example 2 and Example 3 have a current density of 500 mA·cm -2 The overpotentials at the current densities are 168mV, 165mV, and 144mV, respectively; the Pt / C electrode containing precious metal platinum has a current density of 500mA·cm -2 The overpotential under the current density is 331 mV. The overpotential corresponding to the electrode containing the noble metal Pt / C is about twice that of the electrodes prepared in Examples 1-1, 2 and 3 of the present invention.
[0073] Figure 1 and Figure 2 It shows that the nickel-molybdenum alloy electrodes prepared in Examples 1-1, 2 and 3 of the present invention have lower overpotentials for catalytic hydrogen evolution, and their performances are better than those of the Pt / C electrode containing precious metal platinum.
[0074] Figure 3 The X-ray diffraction pattern of the nickel-molybdenum hydrogen evolution catalytic electrode prepared in Example 2 is shown. Figure 3 It can be further explained that the performance of the nickel-molybdenum hydrogen evolution catalytic electrode prepared in Example 2 is slightly better than that of the nickel-molybdenum hydrogen evolution catalytic electrode prepared in Example 1-1. Figure 3 As shown, after adding lauryl alcohol in Example 2, the nickel-molybdenum ratio is less than 2:1, but due to the co-deposition method of the present invention, the prepared catalyst has good crystallinity and can obtain better catalytic activity for hydrogen evolution reaction than precious metal platinum in a relatively wide concentration range.
[0075] Figure 4 The electrochemical active areas of the nickel-molybdenum hydrogen evolution catalytic electrodes prepared in Example 1-1, Example 2, Example 3 and Comparative Example 1, and the Pt / C electrode containing the precious metal platinum are shown. Figure 4 It can be further explained that the performance of the nickel-molybdenum hydrogen evolution catalytic electrode prepared in Example 3 is better than that of the nickel-molybdenum hydrogen evolution catalytic electrode prepared in Example 1-1. Figure 4 As shown, the addition of ethylene glycol in Example 3 can deposit a catalyst with smaller particles at a slower deposition rate, thereby further increasing the electrochemical active area of the catalyst, showing excellent catalytic activity for the hydrogen evolution reaction.
[0076] Figure 5 The polarization curves (100% iR compensation) of the nickel-molybdenum hydrogen evolution catalytic electrodes prepared in Example 1, Example 4 and Comparative Example 1 are shown. Figure 5 As shown, when the current density is as low as 500 mA cm -2 When the current density is greater than or equal to 1A·cm -2 Only when the current density is high can an electrocatalytic electrode with excellent performance be obtained. The technical method of the present invention can obtain a high-performance HER catalytic electrode only under diffusion-controlled deposition conditions, so the catalytic effect of the prepared catalytic electrode has a strong correlation with the current density during the deposition process.
[0077] Figure 6 The constant current stability test of the nickel-molybdenum hydrogen evolution catalytic electrode prepared in Example 2 is shown. In order to further verify the stability of the catalyst in industrial water electrolysis conditions, the catalytic electrode prepared in Example 2 was subjected to a fluctuating water electrolysis stability test. The test process was to periodically adjust the current density, with each cycle at 100 mA·cm -2 The current density was taken as the starting point and increased by 100 mA cm every 1 h. -2 , up to 500mA·cm -2 , under the strongly fluctuating test conditions, the catalyst can still maintain good stability for a long time.
[0078] Fig. 9 The scanning electron microscope images of the nickel-molybdenum hydrogen evolution catalytic electrodes prepared in Example 1-1, Example 1-2, Example 3 and Comparative Example 1 are shown. Fig. 9 It can also be seen that the three conditions of "standing" (Example 1-1), "stirring" (Example 1-2), and "adding ethylene glycol" (Example 3) can all produce nickel-molybdenum alloy self-supporting catalytic electrodes with good performance. -2 When the current density is , the performance of the nickel-molybdenum alloy self-supporting catalytic electrode is poor.
[0079] Example 5
[0080] This embodiment provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0081] (1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0082] (2) Weigh 13.2 g of ammonium sulfate and 1.21 g of sodium molybdate dihydrate, dissolve them in 50-80 mL of water to obtain a colorless transparent solution, then weigh 2.63 g of nickel sulfate hexahydrate, and dissolve it in 20-50 mL of water, mix the two solutions, and add deionized water to make the total volume of the solution 100 mL. After mixing, the solution turns blue-green and generates a green precipitate, which is ammonium nickel sulfate. The concentration of ammonium nickel sulfate in the supernatant is saturated, and the supernatant is used as the electrodeposition solution.
[0083] (3) The clean copper foam obtained above was used as the cathode and the graphite counter electrode was used as the anode, and placed in the above electrodeposition solution at 2A·cm -2 After the deposition is completed, the catalytic electrode is taken out from the electrodeposition solution, washed with deionized water, then washed with ethanol, and left to dry to obtain a nickel-molybdenum alloy self-supporting catalytic electrode.
[0084] Example 6
[0085] This embodiment provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0086] (1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0087] (2) Prepare 100 mL of a solution having a sodium sulfate concentration of 1 mol / L and a nickel sulfate concentration of 0.1 mol / L with deionized water, add 10 g of boric acid, and heat to 60°C to dissolve (since the buffering effect of a saturated solution of boric acid at room temperature is not sufficient to keep the solution stable during the electrodeposition process, the solution is heated to 60°C, and the temperature of the solution should not be lower than 60°C during subsequent operations), then add 1.19 g of sodium molybdate dihydrate and stir to dissolve, thereby obtaining an electrodeposition solution.
[0088] (3) The clean copper foam obtained above was used as the cathode and the graphite counter electrode was used as the anode, and placed in the above electrodeposition solution at 2A·cm -2 After the deposition is completed, the catalytic electrode is taken out from the electrodeposition solution, washed with deionized water, then washed with ethanol, and left to dry to obtain a nickel-molybdenum alloy self-supporting catalytic electrode.
[0089] Example 7
[0090] This embodiment provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0091] (1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0092] (2) 100 mL of a solution having a sodium acetate concentration of 2 mol / L and a nickel sulfate concentration of 0.1 mol / L was prepared with deionized water, and glacial acetic acid was added to adjust the pH of the solution to 4.5. Subsequently, 1.19 g of sodium molybdate dihydrate was added and stirred to dissolve to obtain an electrodeposition solution. The solution was still a green transparent solution without precipitation.
[0093] (3) The clean copper foam obtained above was used as the cathode and the graphite counter electrode was used as the anode, and placed in the above electrodeposition solution at 2A·cm -2 After the deposition is completed, the catalytic electrode is taken out from the electrodeposition solution, washed with deionized water, then washed with ethanol, and left to dry to obtain a nickel-molybdenum alloy self-supporting catalytic electrode.
[0094] Example 8
[0095] This embodiment provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0096] (1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0097] (2) 100 mL of a solution having an ammonium acetate concentration of 2 mol / L and a nickel sulfate concentration of 0.1 mol / L was prepared with deionized water, and then 1.19 g of sodium molybdate dihydrate was added and stirred to dissolve to obtain an electrodeposition solution. The solution was still a green transparent solution without precipitation.
[0098] (3) The clean copper foam obtained above was used as the cathode and the graphite counter electrode was used as the anode, and placed in the above electrodeposition solution at 2A·cm -2 After the deposition is completed, the catalytic electrode is taken out from the electrodeposition solution, washed with deionized water, then washed with ethanol, and left to dry to obtain a nickel-molybdenum alloy self-supporting catalytic electrode.
[0099] Electrochemical tests were performed in 1 mol / L potassium hydroxide aqueous solution using the nickel-molybdenum alloy self-supporting catalytic electrode prepared in Example 5-8 as the working electrode, graphite as the counter electrode, and a mercury / mercury oxide electrode as the reference electrode. Figure 7 The polarization curves (100% iR compensation) of the nickel-molybdenum alloy self-supporting catalytic electrodes prepared in Examples 5-8 and the Pt / C electrode containing precious metal platinum are shown. Figure 7 It can be shown that the catalysts deposited by the general electrodeposition solution configuration method have catalytic performance that exceeds that of Pt / C at high current density.
[0100] Example 9
[0101] Example 9-1
[0102] This embodiment provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0103] (1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0104] (2) Weigh 10.70 g of ammonium chloride and 2.37 g of nickel chloride hexahydrate, dissolve them in 40-50 mL of deionized water, wait for the solution to become clear, add 50 g of glycerol, and stir until homogeneous. Weigh 1.22 g of dihydrate and sodium molybdate, dissolve them in 5-10 mL of water, pour them into the above-prepared solution, stir until homogeneous, and dilute to 100 mL to obtain an electrodeposition solution.
[0105] (3) The clean copper foam obtained above was used as the cathode and the graphite counter electrode was used as the anode, and placed in the above electrodeposition solution at 2A·cm -2 After the deposition is completed, the catalytic electrode is taken out from the electrodeposition solution, washed with deionized water, then washed with ethanol, and left to dry to obtain a nickel-molybdenum alloy self-supporting catalytic electrode.
[0106] Example 9-2
[0107] This embodiment provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0108] (1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0109] (2) Weigh 10.70 g of ammonium chloride and 2.37 g of nickel chloride hexahydrate, dissolve them in 40-50 mL of deionized water, wait for the solution to become clear, add 50 g of glycerol, and stir until homogeneous. Weigh 1.22 g of dihydrate and sodium molybdate, dissolve them in 5-10 mL of water, pour them into the above-prepared solution, stir until homogeneous, and dilute to 100 mL to obtain an electrodeposition solution.
[0110] (3) The clean copper foam obtained above was used as the cathode and the graphite counter electrode was used as the anode, and placed in the above electrodeposition solution at 1 A·cm -2 After the deposition is completed, the catalytic electrode is taken out from the electrodeposition solution, washed with deionized water, then washed with ethanol, and left to dry to obtain a nickel-molybdenum alloy self-supporting catalytic electrode.
[0111] Example 9-3
[0112] This embodiment provides a method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, comprising:
[0113] (1) The copper foam was ultrasonically cleaned with a 1 mol / L hydrochloric acid aqueous solution for 20 min to obtain a clean copper foam.
[0114] (2) Weigh 10.70 g of ammonium chloride and 2.37 g of nickel chloride hexahydrate, dissolve them in 40-50 mL of deionized water, wait for the solution to become clear, add 50 g of glycerol, and stir until homogeneous. Weigh 1.22 g of dihydrate and sodium molybdate, dissolve them in 5-10 mL of water, pour them into the above-prepared solution, stir until homogeneous, and dilute to 100 mL to obtain an electrodeposition solution.
[0115] (3) The clean copper foam obtained above was used as the cathode and the graphite counter electrode was used as the anode, and placed in the above electrodeposition solution at 0.5 A·cm -2 After the deposition is completed, the catalytic electrode is taken out from the electroplating solution, washed with deionized water, then washed with ethanol, and allowed to stand and dry to obtain a nickel-molybdenum alloy self-supporting catalytic electrode 9-3.
[0116] Electrochemical testing was performed in a 1 mol / L potassium hydroxide aqueous solution using the nickel-molybdenum alloy self-supporting catalytic electrode prepared in Example 9 as the working electrode, graphite as the counter electrode, and a mercury / mercury oxide electrode as the reference electrode. Figure 8The polarization curve of the nickel-molybdenum alloy self-supporting catalytic electrode prepared in Example 9 is given (100% iR compensation). After increasing the solution viscosity and limiting the diffusion rate, even if the current is reduced to 0.5 A·cm -2 , the deposited catalyst still has good hydrogen evolution performance, which illustrates the effectiveness of the viscosity-limited diffusion strategy.
[0117] In summary, the nickel-molybdenum alloy self-supporting catalytic electrode preparation process provided by the present invention can use a nickel salt-molybdenum salt-supporting electrolyte mixed solution on the surface of a copper-based metal material and / or a nickel-based metal material, and by regulating the viscosity of the electrodeposition liquid and the deposition current, achieve electrochemical co-deposition of nickel ions and molybdenum ions to obtain a nickel-molybdenum alloy self-supporting catalytic electrode. This "one-step" electrodeposition process for preparing a self-supporting catalytic electrode does not contain precious metals in the raw materials, the operating conditions are easy to control, the industrial process is simple, the safety is good, the energy consumption is low, and it is suitable for large-scale low-cost industrial manufacturing.
Claims
1. A method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode, wherein: include: Placing a copper-based metal material and / or a nickel-based metal material in an electrodeposition solution for electrochemical deposition to obtain a nickel-molybdenum alloy self-supporting catalytic electrode; The electrodeposition solution comprises a nickel salt-molybdenum salt-supporting electrolyte mixed solution; the nickel salt-molybdenum salt-supporting electrolyte mixed solution comprises a supporting electrolyte, a nickel salt and a molybdenum salt; During the electrochemical deposition process, the current density is 1 to 2 A·cm -2 ; or, during the electrochemical deposition process, the current density is greater than or equal to 0.2A·cm -2 , less than 1A·cm -2 The electrodeposition liquid includes a first thickener, and the mass fraction of the first thickener is 10 to 60% based on 100 mL of the electrodeposition liquid being 100%.
2. The method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode according to claim 1, wherein: The electrodeposition solution further comprises a second thickener and / or a surfactant; Preferably, the first thickener and the second thickener are each independently selected from one or a combination of two or more of glycerol, ethylene glycol, sodium carboxymethyl cellulose, xanthan gum, gelatin and sodium alginate; Preferably, the surfactant is selected from one or a combination of two or more of lauryl alcohol, sodium dodecyl sulfate, 4-(1,1,3,3-tetramethylbutyl)phenyl-polyethylene glycol and polyoxyethylene sorbitan monolaurate.
3. The method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode according to claim 2, wherein: Based on 100 mL of the electrodeposition solution as 100%, the mass fraction of the first thickener and the second thickener is 2 to 60%.
4. The method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode according to claim 2, wherein: In the electrodeposition solution, the concentration of the surfactant is 0.2-5 mmol / L.
5. The method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode according to claim 1, wherein: In the electrodeposition solution, the concentration of the supporting electrolyte is 0.5 to 3 mol / L, the concentration of the nickel salt is 0.05 to 2 mol / L, and the concentration of the molybdenum salt is 0.025 to 0.1 mol / L.
6. The method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode according to claim 1, wherein: During the electrochemical deposition process, the electrochemical deposition time is 3 to 120 minutes.
7. The method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode according to claim 1, wherein: The supporting electrolyte is selected from one or a combination of two or more of ammonium salts, sodium salts and potassium salts; Preferably, the ammonium salt is selected from one or a combination of two or more of ammonium acetate, ammonium sulfate and ammonium chloride; Preferably, the sodium salt is selected from one or a combination of two or more of sodium acetate, sodium chloride and sodium sulfate; Preferably, the potassium salt is selected from one or a combination of two or more of potassium chloride, potassium sulfate and potassium acetate.
8. The method for preparing a nickel-molybdenum alloy self-supporting catalytic electrode according to claim 1, wherein: The pH value of the nickel salt-molybdenum salt-supporting electrolyte mixed solution is adjusted to 4.0-6.0 by using a buffer solution; Preferably, the buffer solution is selected from one or a combination of two or more of an ammonium salt solution, a boric acid solution and an acetic acid solution.
9. A nickel-molybdenum alloy self-supporting catalytic electrode, wherein: The nickel-molybdenum alloy self-supporting catalytic electrode is prepared by the preparation method of any one of claims 1 to 8.
10. Use of the nickel-molybdenum alloy self-supporting catalytic electrode according to claim 9 in hydrogen production by water electrolysis, electrochemical reduction of carbon dioxide or electrochemical reduction of nitrate.
Citation Information
Patent Citations
Nickel-molybdenum alloy self-supporting electrode and preparation method and application thereof
CN116145172A
Laser direct-writing synthesized high-current-density electrolyzed water difunctional catalytic electrode and preparation method thereof
CN116752173A